PENGARUH PEMANFAATAN AIR SUNGAI SIAK TERHADAP PENYAKIT DIARE DAN PENYAKIT KULIT PADA MASYARAKAT PINGGIRAN SUNGAI SIAK (KASUS DI KECAMATAN RUMBAI PESISIR PEKANBARU) - Nita Cahyaning; Aras Mulyadi; Thamrin Thamrin (Program Pascasarjana Universitas Riau, 2009)
The research was conducted on May – June 2007 in side of Siak River at Kecamatan Rumbai Pesisir, Pekanbaru. The purposes of research is know that one of the impacts of pollution on Siak River is diseases carrying water had increased (diarrhea and skin diseases). Therefore, itneeded a research concern on the advantage effects of river waters toward diarrhea and skindiseases of community side Siak River (case on Kecamatan Rumbai Pesisir, Pekanbaru). Thehypothesis was that pollution on Siak River caused high prevalence of case on diarrhea and skindiseases, oppositely, the people had not used waters from Siak River had case by lowprevalence. The research design was conducted by cross sectional method where measurementand observation was conducted at the same time (once periodic) and sampling purposively.Then, data analyses got by chi square (X2) to determinate a correlation and the strength wasmeasured by odds ratio (OR) value. The result of analyses was show that toilet activities(bathed, washed and water closet) had proved that people used river water would had higherrisk affected by skin diseases than people had not used it. Bath activities was OR = 1,659 thatmeans people had take bath in Siak River would higher affected by skin diseases 1,659 timeshigher than people had not bath in river. Washed cloth activities was OR= 2.032; washed dishand kitchen tools OR = 1,737 and used water closet OR = 2,217. There was not correlationbetween the toilet activities (bath, wash and water closet) with diarrhea disease; significantly, itcaused diarrhea disease usually affected by drinking water that disturbance of digestive system.But, in this research might not proved correlation between the using drinking water withdiarrhea disease. It might caused by few sample or although people didn’t used the water river as drinking water, directly, but still affected by diarrhea. And people percentage affected bydiarrhea disease was great in 25 percent.